Institusi Sosial Dan Wakaf Sebagai Pilar Peradaban: Analisis Sejarah Pada Masa Utsmaniyah - Fatimah Zahra Mulyasari; Arif Budi Prasetyo; Nabila Khairunnisa (CV JK Riset Publishing Group, 2026)
This study investigates the intellectual traditions and scholarly ethics embedded in the contributions of two towering figures of Islamic civilization, Abu Hamid al-Ghazali and Ibn Rushd (Averroes), within the broader context of classical Islamic epistemology. The research aims to analyze how both thinkers conceptualized the ethics of knowledge production, the boundaries of rational inquiry, and the relationship between reason and revelation as civilizational cornerstones. Employing a qualitative historical-philosophical approach with library research design and comparative textual analysis, this study draws upon primary classical texts and recent Indonesian academic scholarship. The findings reveal that al-Ghazali and Ibn Rushd, despite their famous philosophical disagreement, both affirmed a rigorous intellectual ethics centered on honesty, methodological discipline, and the service of human welfare. Their respective frameworks of Sufistic epistemology and rational demonstration represent complementary rather than contradictory traditions within Islamic intellectual heritage. This study concludes that synthesizing both perspectives offers a productive model for renewing Islamic scholarly culture and resolving the false dichotomy between faith and reason in contemporary Muslim education.